2022
DOI: 10.3390/ijerph192315682
|View full text |Cite
|
Sign up to set email alerts
|

What Influences Farmers’ Adoption of Soil Testing and Formulated Fertilization Technology in Black Soil Areas? An Empirical Analysis Based on Logistic-ISM Model

Abstract: Along with the increasing prominence of environmental risks such as soil surface source pollution and declining quality grade of arable land, the issues of how to address irrational fertilizer application and enhance the safety of agricultural products have attracted widespread attention. In this context, clarifying the main factors affecting farmers’ use of soil testing and formulated fertilization technology (STFFT) can further improve the technology adoption rate and fertilizer utilization efficiency, promo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 68 publications
2
8
0
Order By: Relevance
“…The corresponding marginal effect of 0.004 indicates that for every additional 6.67 ha in planting area, the probability of farmers using organic fertilizer would increase by 0.4%, on average. This outcome is consistent with expectations and supports the earlier empirical findings of Anthoinette et al [30] who concluded that a larger scale of operation can significantly increase farmer ability to input organic fertilizer. The larger the scale of farming operations, the heavier the dependency on agricultural income.…”
Section: Influence Of Other Factorssupporting
confidence: 92%
See 3 more Smart Citations
“…The corresponding marginal effect of 0.004 indicates that for every additional 6.67 ha in planting area, the probability of farmers using organic fertilizer would increase by 0.4%, on average. This outcome is consistent with expectations and supports the earlier empirical findings of Anthoinette et al [30] who concluded that a larger scale of operation can significantly increase farmer ability to input organic fertilizer. The larger the scale of farming operations, the heavier the dependency on agricultural income.…”
Section: Influence Of Other Factorssupporting
confidence: 92%
“…The marginal effects corresponding to the three listed income categories are 0.084, 0.138 and 0.107, respectively, and the probability of adopting organic fertilizer increases by 8.4%, 13.8%, and 10.7%, respectively. A similar effect has been reported by Anthoinette et al [30] . A possible explanation is that a higher annual household income improves affordability and more likely the choice of organic fertilizer.…”
Section: Influence Of Other Factorssupporting
confidence: 90%
See 2 more Smart Citations
“…It is generally accepted that changes in farmers' fertilization behavior are influenced not only by their demographic, psychological, household, and production and business characteristics [2][3][4], but also by external incentives and government regulation [3][4][5]. For farmers, transitioning from traditional fertilization methods to scientific fertilization methods is a complex decisionmaking process to decide whether to adopt new technologies and new products, often relying on multiple information channels to help make decisions [6].…”
Section: Introductionmentioning
confidence: 99%